2022
DOI: 10.1038/s41597-022-01612-y
|View full text |Cite
|
Sign up to set email alerts
|

Absolute protein quantitation of the mouse macrophage Toll-like receptor and chemotaxis pathways

Abstract: The Toll-like receptor (TLR) and chemotaxis pathways are key components of the innate immune system. Subtle variation in the concentration, timing, and molecular structure of the ligands are known to affect downstream signaling and the resulting immune response. Computational modeling and simulation at the molecular interaction level can be used to study complex biological pathways, but such simulations require protein concentration values as model parameters. Here we report the development and application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…For protein copy number estimations, we assumed total protein mass of 230 pg/cell for BMDMs, 78 25 pg/cell for non-stimulated and 75 pg/cell for stimulated T cells. 28 …”
Section: Methodsmentioning
confidence: 99%
“…For protein copy number estimations, we assumed total protein mass of 230 pg/cell for BMDMs, 78 25 pg/cell for non-stimulated and 75 pg/cell for stimulated T cells. 28 …”
Section: Methodsmentioning
confidence: 99%
“…A focus is understanding the array of responses elicited by host cells to prevent the spread of an infection, including immune signaling. In this vein, the use of targeted proteomics defined the absolute numbers of protein molecules per cell in the mouse macrophage pathogen recognition receptor and chemotaxis pathways, providing the means for pathway modeling and simulation . Combinatorial phosphorylation, protein interaction, and microscopy studies have demonstrated that the immune factor IFI16, upon recognition and binding to viral DNA, undergoes phosphorylation-controlled liquid–liquid phase separation that regulates innate immune signaling .…”
Section: Biology and Disease-driven Hppmentioning
confidence: 99%